An Information Security Using DNA Cryptography along with AES Algorithm - et. al., arsha Kolate, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Securing information is the most important need of not only the business world but also it’s highly essential in all the other major sectors. The secured data storage capacity along with security during data transit is also an important factor. In this paper DNA based security technique is proposed as an information carrier, the new data securing method can be adopted by harnessing the advantages of DNA based AES. This technique will provide multilayer security. The proposed system aims to secure transactional data during communication as it is required when message or data transfer between sender and receiver should be confidential along with integrity and availability.AS the data hiding needs a carrier to hold the data, therefore in order to enhance data security and make the data more confidential effective encryption algorithm is proposed using DNA cryptography. DNA molecules, holds an ability to store, process and transfer data, stimulates the notion of DNA cryptography. This amalgamation of the chemical features of genetic DNA structures along with cryptography confirms the non-vulnerable communication. The current features with reference to DNA cryptography are reviewed and presented here.